Burn marks - Paretsky, Sara, 1947- (Virago, 1991)
Someone knocking on the door at 3 A.M. is never good news. For V.I. Warshawski, the bad news arrives in the form of her wacky, unwelcome aunt Elena.The fire that has just burned down a sleazy SRO hotel has brought Elena to V.I.'s doorstep.Uncovering an arsonist -- and the secrets hidden behind Elena's boozy smile -- will send V.I. into the seedy world of Chicago's homeless...into the Windy City's backroom deals and bedroom politics, where new schemers and old cronies team up to get V.I. off the case -- by hook, by crook, or by homicide.